The Challenges in Handling Abandoned Children Based on Pancasila Student Profiles (Case Study at Pondok Al-Hakim Sinar Melati 2) - Ma'arif, Mahmuda Muda; Marzuqi, Yasir; Zulfikar, Muhammad; Hasyim, Iqbal; Setianingsih, Aprilia (Jurnal Kewarganegaraan, 2024)
AbstractThe number of neglected children with social welfare problems in Yogyakarta is still high. This is proven by data for 2021 of 7,902 children and in 2022 of 5,200 abandoned children. The Sinar Melati Sleman Muhammadiyah Islamic Boarding School is one place that accepts abandoned children's social problems. The new independent learning curriculum encourages all educational institutions, including Islamic boarding schools, to be able to implement it. So, this research aims to examine the implementation pattern of the Pancasila Student Profile Program in Pondok al-Hakim Ray Melati 2. This research was conducted using qualitative methods. The subject of this research is the implementation of the Pancasila Student Profile Program at Pondok al-Hakim Ray Melati 2. This research uses Snowball Sampling to search for research data. The results of this research show that efforts to save the profile of Pancasila students have been made in such a way through entrepreneurial activities, pencak silat, scouts, and other religious development activities, but the important thing is that they are still ongoing. So, the next challenge is the need for facilities and infrastructure to maximize P5 activities through orphanages.-----------AbstrakAngka penyandang masalah kesejahteraan sosial anak terlantar di Yogyakarta terbilang masih tinggi, hal ini dibuktikan dengan data 2021 jumlah 7.902 anak dan tahun 2022 sebanyak 5.200 anak terlantar. Pondok Pesantren Muhammadiyah Sinar Melati Sleman salah satu tempat yang menerima masalah sosial anak terlantar. Kurikulum baru merdeka belajar mendorong semua tempat pendidikan termasuk pondok pesantren untuk dapat menerapkannya. Sehingga penelitian ini memiliki tujuan untuk mengkaji pola implementasi Program Profil Pelajar Pancasila di Pondok al - hakim sinar melati 2. Penelitian ini dilakukan dengan metode kualitatif. Subjek dari penelitian ini adalah pelaksanaan Program Profil Pelajar Pancasila di Pondok al - hakim sinar melati 2. Penelitian ini menggunakan Snowball Sampling untuk mencari data penelitian. Hasil penelitian ini menujukan bahwa upaya perwujudan profil pelajar Pancasila telah diupayakan sedemikian rupa melalui kegiatan entrepreneur, pencak silat, pramuka, dan kegiatan pembinaan keagamaan lainya namun sifatnya masih yang penting berjalan. Sehingga kedepan tantangan yang dihadapi adalah perlu fasilitas sarana dan prasarana untuk memaksimalkan kegiatan P5 melalui panti asuhan.